2013
DOI: 10.1007/s00125-012-2804-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 is a key therapeutic target for renal injury in a mouse model of type 2 diabetes

Abstract: Aims/hypothesis As microRNA-21 (miR-21) plays a pathological role in fibrosis, we hypothesised that it may be a therapeutic target for diabetic nephropathy. Methods Abundance of miR-21 was examined in diabetic kidneys from db/db mice. The therapeutic potential of miR-21 in diabetic kidney injury was examined in db/db mice by an ultrasound-microbubble-mediated miR-21 small hairpin RNA transfer. In addition, the role and mechanisms of miR-21 in diabetic renal injury were examined in vitro under diabetic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
291
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(308 citation statements)
references
References 41 publications
(70 reference statements)
14
291
0
3
Order By: Relevance
“…Advances in science have led to the development of nonviral vectors-mediated gene therapies to overcome the shortcomings, e.g. the sleeping beauty transposon system (Aronovich et al 2011) and the ultrasound microbubblemediated gene delivery system (Lan et al 2003, Zhong et al 2013. Transposon-based miR-29b overexpression via mouse tail vein injection resulted in higher levels of transfection and long-term expression of miR-29b in the lungs of mice, without obvious pathological changes (Xiao et al 2012).…”
Section: Discussion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in science have led to the development of nonviral vectors-mediated gene therapies to overcome the shortcomings, e.g. the sleeping beauty transposon system (Aronovich et al 2011) and the ultrasound microbubblemediated gene delivery system (Lan et al 2003, Zhong et al 2013. Transposon-based miR-29b overexpression via mouse tail vein injection resulted in higher levels of transfection and long-term expression of miR-29b in the lungs of mice, without obvious pathological changes (Xiao et al 2012).…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…A study showed that miR-221 could downregulate adiponectin receptor 1 (ADIPOR1)-mediated actions of insulin, possibly via peroxisome proliferator-activated receptor (PPAR) signaling (Meerson et al 2013). An increase in miR-93 in the adipocytes of polycystic ovary syndrome patients diminished the GLUT4 expression by directly binding the 3 0 UTR, indicating the mechanism of insulin resistance in diabetes patients (Chen et al 2013). In addition, studies have shown that many miRNAs were highly associated with insulin resistance in adipose tissue though the directly targeted gene was not identified.…”
Section: Mirnas and Insulin Resistancementioning
confidence: 99%
“…In addition, the pro-fibrotic property of miR-21 is further confirmed by functional analyses as miR-21 positively regulates expression of ECM and -SMA in TECs and MCs after treatment of TGF-1 or under diabetic condition [54,[62][63][64][65]. Overexpression of miR-21 in kidney cells also promotes but knockdown of miR-21 reduces renal inflammation under diabetic condition [63]. The exact mechanism of how miR-21 participates in diabetic renal injury may be related to its putative target genes and the activation of TGF-signaling during diabetic condition [68,69].…”
Section: Mir-192mentioning
confidence: 77%
“…Recently miR-21 expression has been found to be increased in kidney biopsies from diabetic patients compared to healthy controls [66]. In addition, the pro-fibrotic property of miR-21 is further confirmed by functional analyses as miR-21 positively regulates expression of ECM and -SMA in TECs and MCs after treatment of TGF-1 or under diabetic condition [54,[62][63][64][65]. Overexpression of miR-21 in kidney cells also promotes but knockdown of miR-21 reduces renal inflammation under diabetic condition [63].…”
Section: Mir-192mentioning
confidence: 87%
See 1 more Smart Citation